ENGLISH LEARNING MODEL AT ALAM RAMADHANI ELEMENTARY SCHOOL KEDIRI: AN ANALYTICAL EVALUATION - Vina Khoirun Nisa'; Ary Setya Budhi Ningrum; Ria Fakhrurriana (PROJECT (Professional Journal of English Education), 2024)
Ramadhani Elementary School is one of school in Kediri that implements nature-based school. Nature-based school means school that provides nature as the environment for learning. The aim of this research is to find the English learning model, what activities are carried out, and the classroom management implemented at Ramadahi Elementary School Kediri. This research is a qualitative descriptive study which the subjects of this research are students in grades 3 and 4. To find out the English learning model and activities in it, the researcher carries out observations checklist to obtain supporting data. Meanwhile, to find out the management class in the English learning process, the researcher uses interview and documentation as complementary data. The results of this research show that at Ramadhani Elementary School Kediri, the teacher implements an interactive learning model and the learning activities are divided into three stages, namely opening with icebreaking and reviewing material, main activity with studying new material while playing games, and closing as evaluation and giving feedback to students. The classroom management implemented at the Ramadhani Elementary School Kediri is Assertive Discipline. while the factors that support the success of nature-based school are teacher, students, material, and the learning and teaching environment.